2019
DOI: 10.5688/ajpe6745
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Patient Care Through Communication Training in a Pre-clerkship Pharmacy Education Course in Japan

Abstract: Objective. The purpose of this study was to teach communication skills for patient care to preclerkship students and observe changes in student perspectives towards communication pre to post training.Methods. An eight-week training course was taught to all fourth year pre-clerkship students for two consecutive years, using discussions and research, practicing communication skills, making science-based responses, and developing awareness of patient education for lifestyle, selfmedication, quality of life, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Different medication reminder applications on smartphones and electronic watches have been proposed and used by patients. However, using straightforward and clear medical instructions seems to be the simplest approach [ 28 ]. In our study, we found that the relationship between taking medications as instructed by a healthcare provider and having clear medical instructions was significant ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Different medication reminder applications on smartphones and electronic watches have been proposed and used by patients. However, using straightforward and clear medical instructions seems to be the simplest approach [ 28 ]. In our study, we found that the relationship between taking medications as instructed by a healthcare provider and having clear medical instructions was significant ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Oral examination in the form of independent performance on "dagusibu" is a form of exercise to strengthen students' communication skills and confidence. This exam is an initial initiation to support students' ability to conduct drug information services and counsel patients in the future (Epp et al, 2019). Follow-up on student performance is carried out more in-depth by conducting OSCE exams for all students.…”
Section: Learning Outcomementioning
confidence: 99%